Adaptation and Mitigation for Livestock: A Multidisciplinary Approach in Response to Climate Change - Habermann, Birgit; Mulat, Daniel (CGIAR System Organization, 2024)
Blog on the Debre Birhan Univeristy and Livestock and Climate joint workshop. As part of this collaboration, the ILRI team on Pioneer-Positive Deviance (P-PD) organized a seminar for colleagues from Debre Birhan University on the ILRI Addis Abeba Campus to understand the importance of the P-PD approach for enhancing learning between different farm households and the methodologies used by the Intergovernmental Panel on Climate Change (IPCC) for estimating GHG emissions. The program was a mixture of social and biophysical research on climate change.